2017
DOI: 10.18632/oncotarget.20518
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide recovers endothelial function through reconstructing glycocalyx in the balloon-injury rat carotid artery model

Abstract: Disruption of endothelial cell function is a principle event in cardiovascular disease. Accordingly, therapies have mostly focused on repairing the endothelium, but little attention has been paid to the reconstruction of glycocalyx, which covers the endothelium and protects the function of endothelial cells. Sulodexide has a similar glycosaminoglycan structure to glycocalyx, so it is assumed to be effective in remodeling the glycocalyx following damage. We assessed the effect of sulodexide on glycocalyx remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 46 publications
1
38
0
6
Order By: Relevance
“…In the process of smoking‐induced islets injury (Figure ), there was obvious CD68 inflammatory cell infiltration, which caused β cell dysfunction. Our previous study also demonstrated that CD68 inflammatory cells attached to endothelium in diabetes and balloon‐injury carotid artery model, and then induced the process of atherosclerosis . In smoking, we proved that the infiltration of CD68‐positive cells is the trigger mechanism related to hyperglycemia.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the process of smoking‐induced islets injury (Figure ), there was obvious CD68 inflammatory cell infiltration, which caused β cell dysfunction. Our previous study also demonstrated that CD68 inflammatory cells attached to endothelium in diabetes and balloon‐injury carotid artery model, and then induced the process of atherosclerosis . In smoking, we proved that the infiltration of CD68‐positive cells is the trigger mechanism related to hyperglycemia.…”
Section: Discussionsupporting
confidence: 60%
“…The inflammatory factors, ICAM1 and VCAM1, are over‐expressed in inflammatory cells by smoking, which typically mediate the transmigration of CD68 inflammatory cells into islet and the dysfunction of β cells in positive feedback. They also play the role in the development of microcirculation disorder that can decrease the blood flow of islet and deteriorate the dysfunction of β cells . Upon smoking stimulation, these inflammatory responses also can be aggravated by TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there was a 20-fold increase in macrophage uptake in vessel walls when comparing chow fed mice LCAs that were ligated to those that were not ligated. We speculate that beyond 1 week, the disturbance-flow induced decrease in GCX coverage of inner vessel walls would cause grave break down in the barrier against further infiltration of inflammatory cells, causing additional damage and accelerating growth of atherosclerotic lesion 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Typically, there is inherent presence of uniform flow conditions 5 week study, we and our colleagues 5 showed that brachiocephalic artery degradation correlated to substantial lipid uptake leading to atherosclerotic plaque formation. Li et al 16 showed that damage to the GCX favors pathological adhesion and infiltration of macrophages into the vascular wall. Nagy et al 17 demonstrated that inhibiting synthesis of hyaluronan, a major component of the GCX, using 4-methylumbelliferone reduced endothelial GCX and caused increased leukocyte-to-vessel wall adhesion and macrophage retention in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the glycocalyx leads to many disorders, such as increased capillary permeability and interaction of the endothelium with leukocytes and platelets, which predisposes patients to intravascular thrombosis [27]. Chronic administration of sulodexide, which is a mixture of glycosaminoglycans present in the glycocalyx, results in the rebuilding of that structure [28]. Normal structure of the glycocalyx together with reduced expression of PECAM and ICAM-1 in the presence of sulodexide observed in our experiments can significantly reduce interactions between the vascular endothelium, leukocytes, and platelets, which will result in lower risk of intravascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%